Solutions of anisotropic elliptic equations in unbounded domains - Larisa Mikhailovna Kozhevnikova; Anna Alexandrovna Khadzhi (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2013)
In the paper the Dirichlet problem for an anisotropic quasilinear elliptic equations of the second order is considered. The upper estimates for the generalized solution of this Dirichlet problem are received, the closeness is proved for the isotropic case.